Promoting Reflective Practices in Special Education through Action Research: Recommendations from Preservice Teachers - Paula Wenner Conroy (Networks: An Online Journal for Teacher Research, 2014)
In response to research showing the benefits of reflective practices, many personnel preparation programs have sought ways to help teachers-intraining (pre-service teachers) develop reflective practices in their teaching. This has been done by providing multiple opportunities for reflection and scaffolding within a variety of reflective experiences during extensive field and student teaching practicum experiences (Harford & MacRuairc, 2008). One powerful approach for integrating inquiry into teaching and reflection in practice is action research. The purpose of this article article is to provide a description of an effort by faculty to increase teacher reflection in the preparation program area of special education by using action research and to describe pre-service teachers’ responses to the process.